Effect of Sex and Different Housing Systems on the Performance of Japanese Quails under Varying Floor Densities in Puducherry - A E D, Surya Rani; S, Venugopal; D, Sreekumar; P K, Mandal; R, Ganesan (Journal of Meat Science, 2022)
The effect of different management systems on the performance of Japanese quails in Puducherry on live body weight and carcass characteristics of Coturnix quails were examined in this study. A total of 600 birds were utilized for the study in two management systems, cage and deep litter, under varying floor space of 150, 175 and 200 sq. cm per bird. Each system comprised 300 birds with three floor densities and each floor densities had two replicates with 50 birds in each. Six-hundred-day-old quails purchased from local hatcheries were kept on separate cage system and deep litter system under varying floor densities were fed ad libitum. At the end of the 6-week, twelve birds of both sexes equally from each replicate were slaughtered in the Department of Livestock Products Technology (LPT), of the institute and carcass traits were recorded. The carcasses were processed and the live weight, dressed weight, eviscerated weight, giblet weight and inedible parts weights were measured. Higher values were obtained for female quails in respect of live weight, dressed weight, eviscerated weight, giblet weight and inedible parts weight with regard to housing system, cage and deep litter under varying floor densities. The weight of visceral organs also significantly (P
Keywords: Housing system; floor density; carcass traits; live weight; dressed weight